Urban Expansion and Land Cover Changes in the Special Region of Yogyakarta: The Impact of Transportation and Tourist Attractions - Iskandar, Zahara Sitta; Abdurrahman, Umar; Nandi, Nandi (Universitas Pendidikan Indonesia, 2025)
This study examines the relationship between urban expansion and land cover changes in the Special Region of Yogyakarta (DIY), with a focus on the impacts of transportation infrastructure and tourist attractions. Over recent decades, rapid urbanization driven by economic growth, improved transportation networks, and expanding tourism has significantly transformed land use patterns across the province. The development of the Yogyakarta International Airport (YIA) and the improvement of road networks have been key drivers of urban sprawl, particularly in Sleman and Bantul. These areas have experienced the conversion of agricultural land into residential and commercial zones. The expansion of tourist destinations, such as Gunung Merapi and Prambanan, has further accelerated land use changes, intensifying urban growth and putting pressure on local ecosystems. This study utilizes satellite imagery and spatial regression models to examine land cover changes and their drivers, revealing that infrastructure development and the tourism sector play pivotal roles in shaping the region's landscape. The findings underscore the need for sustainable spatial planning policies to mitigate the environmental impacts of urban sprawl and ensure the long-term resilience of DIY's natural resources and cultural heritage.